Cold War Entanglements and Abortion Technology: Writing Yugoslavia into the Global History of Vacuum Aspiration, 1964‐1974. (5th October 2018) - Bogdan, Branka
Abstract : This article centres on the innovation of a now commonly‐used and World Health Organisation (WHO) recommended technique for the termination of first‐trimester pregnancies, vacuum aspiration. I add to the current scholarship that examines reproductive regulation in Eastern Europe and internationally, by writing Yugoslav physicians and innovators into the global story of the technology's development. During the 1960s and 1970s, Yugoslav physicians played an instrumental role in the innovation of vacuum aspiration. Physicians operated under the party‐endorsed political and ideological aegis of family planning and the state used family planning to build a self‐image of a modern and progressive state in the international Cold War context. In their public rhetoric, physicians attributed scientific advances to the modern nature of the state's distinct style of socialism, the Yugoslav way. The state, in turn, utilised domestic medical innovation and social policy to elevate Yugoslav socialism around the world. While the Yugoslav way was not exceptional, Yugoslavia's atypical geopolitical positioning after the Second World War offered Yugoslav gynaecologists and medical innovators the unusual opportunity to research methods and techniques, and propagate their findings abroad.